2019
DOI: 10.3201/eid2502.171974
|View full text |Cite
|
Sign up to set email alerts
|

Trends of Human Plague, Madagascar, 1998–2016

Abstract: Madagascar is more seriously affected by plague, a zoonosis caused by Yersinia pestis, than any other country. The Plague National Control Program was established in 1993 and includes human surveillance. During 1998–2016, a total of 13,234 suspected cases were recorded, mainly from the central highlands; 27% were confirmed cases, and 17% were presumptive cases. Patients with bubonic plague (median age 13 years) represented 93% of confirmed and presumptive cases, and patients with pneumonic plague (median age 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
62
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(68 citation statements)
references
References 33 publications
5
62
0
1
Order By: Relevance
“…Madagascar has become the country with the highest plague burden [4]. Between 1998 and 2016, 250 to 1500 suspected cases were reported annually by the Malagasy Central Laboratory for Plague, with 18% case-fatality rates for confirmed and presumptive case-patients (1,057/5,819) [5]. The bubonic plague is the most encountered form (about 80%), however, secondary pneumonic plague can lead to overwhelming urban epidemic, such as reported in the capital in 2017 [6,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Madagascar has become the country with the highest plague burden [4]. Between 1998 and 2016, 250 to 1500 suspected cases were reported annually by the Malagasy Central Laboratory for Plague, with 18% case-fatality rates for confirmed and presumptive case-patients (1,057/5,819) [5]. The bubonic plague is the most encountered form (about 80%), however, secondary pneumonic plague can lead to overwhelming urban epidemic, such as reported in the capital in 2017 [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Traditional outdoor granaries are infrequently used due to thief problems. Crops and food are stored in the bedroom, which promotes contact between humans, rodents and their fleas [5,8]. Two flea species have been reported as confirmed vectors.…”
Section: Introductionmentioning
confidence: 99%
“…The rapid diagnostic test (RDT) as point of care (POC) strategy was implemented in Madagascar in 2002 in primary care facilities based in the “endemic districts” together with information provided to community health workers. This RDT has been widely used and improved the specificity of diagnosis, resulting in a drop in the number of suspected cases of bubonic plague [ 64 ]. The RDT is based on monoclonal antibodies against the F1 capsular antigen of Y .…”
Section: Which New Diagnostic Tools For Plague Are Needed?mentioning
confidence: 99%
“…Moreover, it was reported that Y. pestis can survive for at least 24 days in contaminated soil under natural conditions ( Eisen et al, 2008 ), hence creating a potentially natural-born contaminated area in case of the death of a sporadically infected animal. Plague is present in different parts of the world; recent outbreaks were reported in Uganda ( Respicio-Kingry et al, 2016 ), China ( Shi et al, 2018 ), Democratic Republic of Congo ( Abedi et al, 2018 ), and Madagascar ( Andrianaivoarimanana et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%